2000
DOI: 10.1051/forest:2000119
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between forest stands and microclimate: Ecophysiological aspects and consequences for silviculture

Abstract: -At a local scale, forest trees and stands have a marked influence on climate; thus it is possible to define microclimates. These effects depend on local climatic characteristics and stand type. All climatic parameters should be considered, but particular attention should be paid to temperature, light and water. From a silvicultural point of view knowledge of the interactions existing between microclimatic conditions and stands, in conjunction with information now available concerning tree ecophysiology make i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
370
5
48

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(442 citation statements)
references
References 86 publications
19
370
5
48
Order By: Relevance
“…This difference increased with increasing site xericity. The buffer effect on environmental conditions provided by dominant tree canopy (Aussenac 2000) could be more important at water-limited sites, thereby explaining that the suppressed trees at our study site are less sensitive to the inter-annual water balance variability. In another view, the lower growth sensitivity of suppressed trees is due to a loss of plastic capacity in those trees strongly constrained by competition (Linares et al 2010).…”
Section: Crown Class Modulation Of the Climate-growth Relationshipmentioning
confidence: 97%
“…This difference increased with increasing site xericity. The buffer effect on environmental conditions provided by dominant tree canopy (Aussenac 2000) could be more important at water-limited sites, thereby explaining that the suppressed trees at our study site are less sensitive to the inter-annual water balance variability. In another view, the lower growth sensitivity of suppressed trees is due to a loss of plastic capacity in those trees strongly constrained by competition (Linares et al 2010).…”
Section: Crown Class Modulation Of the Climate-growth Relationshipmentioning
confidence: 97%
“…Firs in general are considered to have a higher ability to maintain a positive carbon balance at low light intensities than spruces [1,18,21,32]. This difference has been primarily attributed to a higher morphological plasticity in relation to light [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding how these traits vary in relation to interacting factors is important in order to promote and assure effectively natural regeneration [1]. Several studies have shown that the effect of light on crown, shoot and needle morphology differs among tree species, with shade-tolerant species typically showing greater morphological changes along a light gradient than do the more shade-intolerant species [4,7,8,12,33].…”
Section: Introductionmentioning
confidence: 99%
“…Consideraram-se duas categorias distintas para a cobertura florestal nativa e outra para a floresta exótica por terem diferentes características de cobertura do solo ocasionando diferentes taxas de escoamento superficial. Na categoria floresta exótica, considerando-se somente a cobertura do solo, o escoamento é superior à floresta nativa, pois as práticas da silvicultura local utilizam uma maior densidade de árvores que diminuem a luminosidade no sub-bosque, principalmente no primeiro decênio de cultivo (Aussenac, 2000). O maior sombreamento ocasiona uma diminuição na cobertura do solo por plantas, principalmente das espécies de gramíneas que possuem a fotossíntese com o ciclo do ácido dicarboxílico C4, e estas requerem uma maior energia luminosa e temperatura para seu pleno desenvolvimento (Odum, 1988).…”
Section: Figuraunclassified